Development of therapeutic genome engineering in laminin-α2-deficient congenital muscular dystrophy. Issue 1 (14th March 2019) - Kemaladewi, Dwi U.; Cohn, Ronald D.
Abstract: Muscular dystrophies are a heterogeneous group of genetic muscle diseases that are often characterized by pathological findings of muscle fiber degeneration and the replacement of muscle fibers with fibrotic/connective tissues. In spite of the genetic causes of many of these conditions having been identified, curative treatments are still lacking. Recently, genome engineering technologies, including targeted gene editing and gene regulation, have emerged as attractive therapeutic tools for a variety of muscular dystrophies. This review summarizes the genome engineering strategies that are currently under preclinical evaluation for the treatment of LAMA2-deficient congenital muscular dystrophy. In particular, we focus on the applications of CRISPR/Cas9 to correct a splice site mutation in LAMA2 and to up-regulate a disease-modifying gene LAMA1 . Finally, the challenges faced in the clinical translation of these strategies are discussed.